The transsexualization process in the Unified Health System and through alternative ways in a given region of Minas Gerais (Research, Society and Development, 2022)
To improve the understanding of the challenges to health care for the Brazilian transgender population, further political-scientific investigations are needed. In view of the elucidated context, this article aims to analyze the structuring of the lines of care involved in the construction of formal and informal paths for the transsexualization process. Specifically, data referring to the health micro-region of a city in Minas Gerais were analyzed, from the perspectives of professionals who work in the implementation of this health care. It is, therefore, an observational, cross-sectional and analytical study with a qualitative approach. The methodology is based on data collection through semi-structured virtual interviews, with interpretation of findings based on content analysis. The verified results indicate a care network with persistence of the pathologization of transsexuality, punctuated by lack of knowledge on the subject, with the presence of social stigma to people who do not fit the Western binary heteronormative pattern. In addition, the interviewees pointed out difficulties and absences in the structuring of services to carry out the transsexualization process in the region in question. It is known that this context directly influences the illness of the people involved, whether due to discrimination and violence, or due to the difficulty of accessing comprehensive health care in their region. This aspect makes the transgender population resort to other ways as an alternative to carry out the transsexualizing process.